Biotechnology in reproductive biology - Hahn, S.K.; Bai, K.V.; Asiedu, Robert; Dixon, Alfred G.O.; Tavoletti, S.; Mariani, A., Veronesi, F.; Tuyl, J.M. van; Creji, M.G.M. van; Dien, M.P. van; Kerckhoffs, D.M.F.Y; Laublin, G.; Brault, M.; et al. (1992)
Plant reproduction is a core process in plant breeding. For decades, one can even say for centuries, plant reproductive biology has largely been a matter of observation, description, and philosophical speculation. Only in the last two decades has it entered the experimental phase, and it is in the last decade that tools are emerging that allow manipulation of plant reproduction for the sake of human needs and goals.